Caries arrest and lesion appearance using two different silver fluoride therapies on primary teeth with and without potassium iodide: 12‐month results. Issue 4 (28th December 2020) - Turton, Bathsheba; Horn, Rithvitou; Durward, Callum
Abstract: Background: Globally, has been an increase in the use of silver fluoride products to arrest carious lesions and a variety of products are available. Objectives: To examine differences in caries arrest and lesion colour of primary tooth carious lesions. Material and Methods: A four‐armed, parallel‐design cluster‐randomised controlled trial which investigated four protocols for caries arrest at 6m and 12m. Children in Group 1 and Group 2 received Rivastar Silver Diammine Fluoride (SDF), and children in Group 3 and Group 4 received a stabilised aqueous silver fluoride solution (AgF). Children in Group 2 and Group 4 received an additional application of KI immediately after the fluoride. Differences in caries arrest and lesion appearance were examined at 6m and 12m using two level logistic regression modelling. Results: The arrest rate varied by group membership; group 1 and group 3 had higher arrest rates (77.3% and 75.3% respectively) than group 2 and group 4 (65.4% and 51.2% respectively). The use of KI was also associated with lower odds of arrest (12m OR 0.25; CI 0.19, 0.34) and higher odds of avoiding black discolouration (12m OR 6.08; 2.36, 15.67). Conclusions: Globally, has been an increase in the use of silver fluoride products to arrest carious lesions and a variety of products are available. This study demonstrated that both AgF and SDF can effectively arrest carious lesions on primary teeth. The use of KI is associated with poorer caries control but better aesthetic outcomes.